SARS-CoV-2 and Subacute Thyroiditis: A Case Report and Literature Review - Amir Mohammad Salehi; Hossain Salehi; Hossein Ali Mohammadi; Jamileh Afsar (Case Reports in Medicine)
Introduction. Subacute thyroiditis (SAT) is an inflammatory disorder of the thyroid gland, usually triggered by a recent viral or bacterial infection of upper respiratory tracts. The disease is characterized by neck pain radiating to the ears and thyroid gland tenderness. In most cases, it is associated with a transient episode of hyperthyroidism, which is followed by euthyroidism. However, sometimes, it manifests itself with hypothyroidism. Case Presentation. The present report described a case of SAT who was a 55-year-old man presenting to an endocrine clinic with tachycardia, tremor, and neck pain radiating to the jaw and ears. His thyroid function test revealed thyrotoxicosis, and thyroid ultrasound findings were consistent with SAT. The patient reported a history of COVID-19 about 15 days before presentation, which was confirmed by a positive PCR test for SARS-CoV-2. Conclusions. It is of great importance for physicians to note that thyrotoxicosis in a patient with a recent history of COVID-19 can be due to SAT. Therefore, they should not begin antithyroid drugs without ordering proper investigations.